PRODUCT QUALITY AFFECTS PURCHASING DECISIONS (Jurnal Kendali Akuntansi, 2023)
The number of coffee lovers in this millenal era is rapidly increasing, and this fact has become the focus of attention for business actors. This fact has been proven by the increasing number of coffee consumption in Indonesia (Sari, Tety, & Eliza, 2016). Data from Association of Indonesian Coffee Exporters and Industries (2017) shows that in 2010, coffee demands in Indonesia reached 190 millions kg, and in 2016 that number increased to 300 million kg, increased nearly 70% in just seven years. Indonesian people’s habits to gather together for chatting and enjoying a cup of coffee has now become Indonesian life style (Cita, 2015). This is in line with the growth of cafes in Indonesia, which is now amounting to more than 10.000 cafesand is predicted to continue to grow. In 2013-2017, the total revenue from cafe sector was estimated to increase from USD 3.4 billions to USD 4.16 billions. These facts prove that the number of coffee lovers in Indonesia is growing, since having coffee as breakfast or for afternoon break, either before or after activities, has become a routine for Indonesian people (Sudiyarto, Widayanti, & Kresna, 2012).